Search for potential gastric cancer markers using miRNA databases and gene expression analysis - Volkomorov, V.; Grigoryeva, E.; Krasnov, G.; Litviakov, N.; Tsyganov, M.; Karbyshev, M.; Zavyalova, M.; Afanasyev, S.; Cherdyntseva, N.; Lisitsyn, N.; Beresten, S. (Experimental Oncology, 2013)
Aim: The aim of this study was to identify genes that are differentially expressed in gastric tumors and to analyze the association of their expression level with tumor clinicopathologic features. Methods: In the present research, we used bioinformatic-driven search to identify miRNA that are down-regulated in gastric tumors and to find their potential targets. Then, the expression levels of some of the target mRNAs were investigated using reverse transcription polymerase chain reaction (RT-PCR) analysis. Results: As a result of the bioinformatics analysis, fifteen genes were found to be potentially differentially expressed between the tumors and normal gastric tissue. Five of them were chosen for the further analysis (WNT4, FGF12, EFEMP1, CTGF, and HSPG2) due to their important role in cell proliferation and differentiation. Expression levels of these genes were evaluated in our collection of frozen tissue samples of gastric tumor and paired normal stomach epithelia. Increased FGF12 expression was observed in diffuse type of gastric cancer while WNT4 mRNA was found to be down-regulated in intestinal type of gastric cancer. Besides, CTGF gene overexpression was revealed in diffuse type of stomach cancer in comparison with that in intestinal type. Up-regulation of CTGF was also associated with lymph node metastasis. Conclusions: The findings show its expedient to perform further investigations in order to clarify diagnostic and prognostic value of CTGF, FGF12, and WNT4’s in stomach cancer as well as the role of these genes in carcinogenesis.